2019
DOI: 10.1038/s41433-019-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

National incidence of eyelid cancer in Ireland (2005–2015)

Abstract: Aims We report on the incidence of cutaneous eyelid tumours in Ireland over the 11-year-period from 2005 to 2015, we identify associations between demographic factors and cutaneous eyelid tumour risk. Methods Skin cancers, including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), melanoma, and other cancers, located on the eyelid or canthus according to ICD-10 coding, as registered by the National Cancer Registry of Ireland (NCRI), were captured from the period 2005 to 2015. Age standardised rates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
3
15
2
1
Order By: Relevance
“…In Ireland, the incidence of BCC is higher in men after the 60 s 7 ; however, women experienced a higher average annual incidence increase compared to men. 3 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ireland, the incidence of BCC is higher in men after the 60 s 7 ; however, women experienced a higher average annual incidence increase compared to men. 3 6 …”
Section: Discussionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is the most common skin cancer in the human population, 1 2 3 and it is also the most common malignant eyelid tumor in Western countries. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The rising incidence of cutaneous melanoma was reported by Paulson et al [ 21 ] and Yang et al [ 22 ]. Previous studies reported the age-adjusted incidence of eyelid melanoma: 0.08 cases per 100 000 individuals per year from 1976 through 1990 by Cook et al 0.6 per million Whites older than 20 years in the 1990s by Margo et al 0.1 per 100 000 overall in Ireland from 2005 to 2015 by Quigley et al [ 8 , 23 , 24 ]. The rising incidence rate in America may be due to inadequate efforts to take measures for sun protection (e.g., sunglasses) and population growth.…”
Section: Discussionmentioning
confidence: 99%
“…Making use of cumulative data storage, the conduction of studies that go beyond case reports is enabled and further information about the individual diseases may be gained. As a consequence, an improvement of treatment options can be achieved [320][321][322]. Only a careful collecting and documentation of all necessary diagnostic criteria such as anamnesis, clinical findings, imaging, laboratory and results of microbiological, histological and, with increasing importance, molecular pathological and genetic examinations enable a reliable diagnosis and an adequate treatment.…”
Section: Acknowledgementsmentioning
confidence: 99%